ANALISIS DAYA SAING DAN FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI EKSPOR TEKSTIL DAN PRODUK TEKSTIL INDONESIA - Sarasgita, Ni Luh; Karmini, Ni Luh (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
The purpose of this study is to determine the competitiveness of the Textile Products and Textile Products (TPT) of Indonesia and factors that affect the value of the export in 7 years. The data used in this study are secondary data of 35 data consisting of time series and cross section data. The analysis techniques used are Revealed Decorative Advantage (RCA) and multiple linear regression. The results showed that Indonesia's competitiveness to the destination country is still low in that period, with the average value of RCA <1. The results also show that simultaneously competitiveness, economic distance, non-tariff measures and GDP state in purpose of the export value of Indonesian TPT. Partially competitiveness has no significant effect on the export values of Indonesian TPT, the distance for negative and significant effect on the TPT Indonesia, with the GDP State of goals that can mode of economic distance on TPT Indonesia, and non-tariff measures is able to affect the export value of TP Indonesia every one in the goal countries.